Evaluation and Assessment of the Indonesian Language in Elementary Schools: Language Content Analysis - Andi Erwin Ali Cappa; Rahma Ashari Hamzah (Program Studi PGSD Universitas Madako Tolitoli, 2024)
Evaluation and assessment are an important part of teaching, aiming to measure students' understanding and monitor their progress in children's language learning. This study examines the purpose and function of evaluation carried out by teachers in monitoring student progress, especially in the context of the content structure and language vocabulary used by students in elementary schools. The method used is language content analysis, focusing on daily tasks involving the preparation of sentence structure and vocabulary selection. The subject of the research is grade V students at UPT SPF SD Inpres Tamalanrea 5 Makassar, with a qualitative approach. The results of the study show that evaluation plays a role not only in providing information about student progress, but also as a tool to improve the quality of learning and encourage students and teachers to continue to improve the learning process for better achievement of goals. The contribution of this research is to provide insight into how evaluation based on sentence structure analysis, vocabulary construction, and grammatical stimulates the improvement of students' language skills in elementary school, as well as provide a deeper understanding of how evaluation can be optimally integrated in learning activities to encourage the development of students' language skills.